(untitled) (Revista Espinhaço, 2023)
The Southern Espinhaço mountain range harbors enormous biodiversity, with a vegetation typically dominated by grassland formations (campos rupestres and campos limpos) speckled with forest formations (capões de mata). This study aimed to evaluate the flowering temporality in areas of dry and wet (where peatlands occur) campos limpos, in order to highlight the temporal variation in plant reproductive characteristics (flower collor) and the effect of anthropization. Some of the studied sites were protected by the Rio Preto State Park, a nature conservation site of full protection, whereas the other sites were adjacent, but outside the conservation unit and subject to anthropization by grazing and fires. The sites were monthly evaluated for collecting botanical material and registering flowering species, being placed in six color categories (white, yellow, orange, red, pink/purple and blue). The protected area presented higher species richness (96) than the unprotected sites (83), although sampling stability was not reached in the collector curves. Most species presented annual flowering events, with more than half of the species being observed in a single month, concentrated in the rainy season, indicating an annual “flowering season”. White was the dominant collor (especially in Asteraceae and Eriocaulaceae), followed by pink/purple (Melastomataceae) and yellow (Asteraceae and Xyridaceae). While the collors associated with generalist pollinators (white and yellow) presented a markedly seasonal flowering, the flowers associated to more specialized systems (red and orange) apparently presented a more continuous flowering over time.